2012
DOI: 10.2807/ese.17.05.20072-en
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of Mycoplasma pneumoniae infection in Finland, 2010–2011

Abstract: The number of cases of Mycoplasma pneumoniae infection detected by laboratory-based surveillance increased in Finland in late 2010. During 2011, the number of cases was four times higher than during the previous epidemic in 2005. The 2011 epidemic affected mostly school-age children. The increased number of cases was probably not due to changes in laboratory procedures, but public interest may have had an effect, since the number of Google queries followed closely the epidemic curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
2
26
0
11
Order By: Relevance
“…Data from Denmark as presented earlier and in this issue [9,23] and Sweden [24] suggests that the epidemic wave started in 2010. With the results from our study, however, we cannot assess whether the reported increases fit into the expected four-to-sevenyear epidemic waves even though this seems to be indicated by data from Finland, Norway and Denmark in this issue [23,25,26]. Institutional settings: infection control guidance for institutional care settings and nosocomial outbreaks, including respiratory tract infections.…”
Section: Resultsmentioning
confidence: 90%
“…Data from Denmark as presented earlier and in this issue [9,23] and Sweden [24] suggests that the epidemic wave started in 2010. With the results from our study, however, we cannot assess whether the reported increases fit into the expected four-to-sevenyear epidemic waves even though this seems to be indicated by data from Finland, Norway and Denmark in this issue [23,25,26]. Institutional settings: infection control guidance for institutional care settings and nosocomial outbreaks, including respiratory tract infections.…”
Section: Resultsmentioning
confidence: 90%
“…Однако в ряде случа ев может регистрироваться и в других возрастных ка тегориях [1][2][3][4]. Среди респираторных проявлений инфекции, вызванной M. pneumoniae, -фарингит, трахеит, трахеобронхит [1,5,6]. У 3-10 % больных развивается внебольничная пневмония (ВП) [3,7].…”
Section: заметки из практикиunclassified
“…Изменения многолетней и сезонной циркуляции микоплазмы в естественных условиях определяют эпидемиологические особенности данного возбуди теля [1,8]. Распространение инфекции, вызванной M. pneumoniae, носит характер вспышек, которые ре истрируются в разных странах с интервалами 3-7 лет и продолжаются в течение нескольких лет (1-3 года) с максимальным подъемом заболеваемости в осен не зимний период [1,2,9].…”
Section: заметки из практикиunclassified
See 1 more Smart Citation
“…M. pneumoniae may cause other serious extrapulmonary sequelae, such as encephalitis (2). The pathogen is found in all age groups, with a higher prevalence in children age 5 to 14 years (3,4). Admissions to a United Kingdom hospital in patients with CAP that were attributed to M. pneumoniae were estimated at 18% in 1982 and 4% in 1999 (5).…”
mentioning
confidence: 99%